SOUS VIDE TECHNOLOGY — SEVERAL ASPECTS OF QUALITY AND MICROBIOLOGICAL SAFETY - Tatyana S. Fofanova (Теория и практика переработки мяса, 2018)
Worsening of the demographic situation (a decline in the birth rate, a growth in the proportion of the elderly and so on), changes in eating  habits associated with the changes in the pace of life, a desire of the  increasing number of people to consume «healthy» products and not to spend much time on their preparation led to an increase in the  demand for convenient ready-to-cook meat products that retain  healthy components. As a result, the minimal processing  technologies such as sous vide are finding ever increasing use. Sous  vide is a technology of low temperature thermal processing of food  under vacuum. Preparation of food by sous vide technology allows  reliable control of product sensory indicators and microbiological  safety with strict adherence to the temperature-time regimes of processing and storage taking into consideration the fact that relatively mild thermal processing may not ensure death of all  vegetative cells and does not inactivate spores. To enhance the  microbiological safety of these products, several additional methods  of treatment with the use of natural antimicrobial substances can be  applied. The paper presents a review of scientific studies aimed at  investigation of an effect of the sous vide technology on changes in  quality indicators and microbiological safety of sous vide products.